Management of 3 Avulsed Permanent Teeth: Case Report of a 3-Year Follow-up - Soukaina El Kharroubi; Sofia Drouri; Bouchra Doumari; Sara Dhoum; Hafsa El Merini (Case Reports in Dentistry)
Dental avulsion is one of the most serious dental injuries. When the tooth is knocked out, the blood supply to the pulp is interrupted and the periodontal ligament cells are exposed to injuries caused by the external environment. In recent years, research findings have shown the possibility of complete healing under favorable conditions: replanting the tooth according to the criteria required by the guideline such as the extra oral time which should be very short, the time of pulp removal after replantation, and the appropriate storage medium. This set of criteria may lead to a slower progression of the phenomenon of resorption with a better prognosis over time; however, there is a high risk of complications such as external root resorption which lies in late replantation. The research results of many research-groups around the world have given us a better understanding of healing and complications. Nowadays, even teeth that are replanted after a delay can be saved. The dentist remains the key person in the case of dental trauma, namely, dental avulsion as his role is the management of the emergency situations. The objective of this case study is to present a successful management of 3 avulsed permanent incisors, replanted and remained with no complications for over a period of 3 years.